Theoretical approaches to the linguistic functions of emoji in digital communications: as metaphor, gesture, and annotation - Ferrari, Enrique (Escritura e Imagen, 2024)
To enhance understanding of the linguistic nature of emojis, their effect on accompanying text has been examined through comparison with other linguistic elements that have been more extensively studied in academic literature. Traditionally emojis have been intuitively understood as visual and conceptual metaphors, however, this overlooks significant differences in their mechanisms that have received little attention in academic discussions. More recent studies have offered an alternativeconceptualisation which equates the function of emojis to that a form of non-verbal language such as gestures. Despite this, there remains a lack of research on emojis’ specific characteristics as a written code, acting as a transcription of those gestures in non-verbal communication. Building on this, the findings of this study illustrate that emojis can be understood as visual representations that signify not the gesture itself but its absence. They serve to alert the reader, who must imagine or infer the gesture within the context of oral communication, thus performing a function similar to stage directions in theatre.
Keywords: Emoji; Digital communication; Metaphor; Idiom; Gesture